(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
The author presents and discusses the debate on indigenous infanticide in Brazil, an issue that has become the subject of several bills in the Brazilian Congress. Moreover, the analysis takes into account other cases regarding traditional practices that conflict with human rights, such as female genital mutilation. The comparison illustrates the possibility of realizing human rights within traditional communities in a dialogical, democratic and unconstrained way. Thus, both individual rights and the collective value of ethical identities are simultaneously protected. Finally, the argument clarifies, in theoretical and practical terms, the alleged impasse between universal human rights and cultural relativism so commonly raised in the public sphere.